2016
DOI: 10.2485/jhtb.25.213
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Two Surgical Methods in Treating Stage IIIb Lunate Necrosis

Abstract: This study aims to determine the biomechanical changes and basis for treatment using two surgical methods (scaphotrapeziotrapezoid [STT] fusion and capitoscaphoid [CS] fusion) for stage IIIb lunate necrosis. Eighteen fresh frozen upper extremities of adult cadavers were randomly divided into three groups. In group A, only the radioscaphoid and radiolunate spaces were exposed to place pressure sensors. Groups B and C underwent STT and CS fusion, respectively. The advanced I-scan pressure measurement system was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…20 Li et al stated in a recent biomechanical study that compared with SCA, STT arthrodesis has much greater value in preventing rotatory semidislocation of the scaphoideum, as well as in maintaining the stability of the wrist. 21 In the present study, SCA was applied following lunatum excision in all patients without significant change in carpal height.…”
Section: Discussionmentioning
confidence: 78%
“…20 Li et al stated in a recent biomechanical study that compared with SCA, STT arthrodesis has much greater value in preventing rotatory semidislocation of the scaphoideum, as well as in maintaining the stability of the wrist. 21 In the present study, SCA was applied following lunatum excision in all patients without significant change in carpal height.…”
Section: Discussionmentioning
confidence: 78%
“…SCA and STT arthrodesis shift the load bearing from radiolunate to radioscaphoid joint along with reduction of force transmission at lunocapitate joint. 35 The principle behind SCA in stage III is to arthrodese scaphoid in a favorable position so as to take load off lunate and reduce the nociceptive stimuli arising out of it. 8 SCA was done in all patients in this study with significant change in Note: values are expressed as mean AE standard deviation (range).…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical investigations have demonstrated that in addition to capitate-hamate-arthrodesis (CHA), SCA and STT arthrodesis resulted in a noteworthy reduction in loading on the lunate [ 13 ]. In a recent biomechanical investigation, Li et al reported that STT arthrodesis is significantly more valuable than SCA in preventing rotatory semi-dislocation of the scaphoid and preserving wrist stability [ 14 ]. In this instance, the patient had SCA after having their lunate removed, and their carpal height did not significantly change.…”
Section: Discussionmentioning
confidence: 99%